(untitled) (Laisvalaikio tyrimai, 2025)
Relevance and novelty. The rapidly changing social and technological environment has a significant impact on the lifestyle and physical activity of the younger generation. Scientific research shows that the lack of movement in adolescents is becoming an increasingly relevant public health problem, which is associated with declining physical capacity, overweight, psychological difficulties, and lack of motivation to participate in active activities (Ostermeier et al., 2024; World Health Organization, 2021). During the winter period, opportunities for physical activity in the natural environment are significantly reduced, therefore it is necessary to promote winter sports, such as cross-country skiing, which can help maintain and strengthen the health and motivation of young people to move (Babaei-Zarch et al., 2024). Although cross-country skiing has obvious physiological and psychological benefits, the impact of this sport on the health and physical activity of adolescents is still insufficiently studied, especially in Lithuania. Therefore, it is relevant to systematically analyse the role of cross-country skiing in the health promotion and development of adolescents (Hoffman & Clifford, 1992). Cross-country skiing is a full-body workout that combines endurance, coordination, and strengthening of the respiratory and cardiovascular systems. This sport can become not only an effective health promotion tool, but also a motivational education tool for adolescents, encouraging them to know the joy of movement, experience togetherness, and develop responsibility for their health. Scientific problem. Although the importance of physical activity for the health of adolescents is well known, recently their lack of physical activity, which negatively affects both physical and mental health, has been increasingly noted. Despite the fact that physical activity education among adolescents is widely recognised as an important health promotion tool, the level of physical activity significantly decreases during the winter season due to limited opportunities to engage in outdoor sports (Ostermeier et al., 2024). Especially in the winter period, when opportunities for active activities in the natural environment decrease, adolescents become less active. Cross-country skiing is a complex form of physical activity that can effectively promote the physical and mental health of adolescents, but there is a lack of theoretical and empirical research that comprehensively examines the benefits of this sport and the possibilities of integrating it into the educational process (Hoffman & Clifford, 1992; Babaei-Zarch et al., 2024). Therefore, there is a need to analyse the impact of cross-country skiing on the strengthening of physical activity and motivation of adolescents more thoroughly, as well as to assess the possibilities of its application in the educational system. Research object. The processes of physical activity and health strengthening of adolescents (14–16 years) related to the practice of cross-country skiing. The aim of the article is to reveal the importance of cross-country skiing for the health and physical activity of adolescents aged 14–16. The physiological, psychological, and educational aspects shall be analysed, and the importance of integrating this activity into the general education process emphasised. Methods. 1. Analysis and research of scientific literature; 2. Data analysis and processing. Results. The winter season significantly reduces the level of physical activity among adolescents, as opportunities for outdoor activities in the natural environment become limited. Cross-country skiing, as a winter sport, plays an important preventive role, allowing to maintain and promote the physical activity and health of adolescents during the winter months. By promoting this activity, the effects of winter inactivity, which can lead to a decrease in physical capacity, overweight, and psychological difficulties, are reduced. Therefore, promoting winter physical activity through cross-country skiing is an important tool to ensure consistent maintenance of physical activity throughout the year. Keywords: cross-country skiing, physical activity, health, adolescents, education, motivation, winter sports.